BokSmart rugby safety education courses are associated with improvements in behavioural determinants in attending coaches and referees: presurvey–postsurvey study. Issue 4 (24th August 2020) - Brown, James Craig; Hendricks, Sharief; Lambert, Michael Ian; van Mechelen, Willem; Verhagen, Evert
Abstract : Background/aim: BokSmart is a nationwide injury prevention programme that aims to reduce players' injury risk mainly through education of coaches and referees in mandatory biennial education courses. These courses are held throughout each rugby season. The objective of this cross-sectional study was to assess whether these courses were associated with improvements in attendees' behavioural determinants. Methods: Coaches and referees completed a questionnaire based on the theory of planned behaviour, immediately before and after their 2012 BokSmart courses. Twelve behavioural determinants were assessed on a five-point Likert scale and open-ended questions. A meaningful change was defined as an improvement of ≥1 unit score supported by null hypothesis testing. Odds of improving by ≥1 unit score (compared with not improving) were assessed in attendees using multivariate logistic regression. Results: In total, 390 coaches and 74 referees completed both questionnaires. 'Before' scores were high for most outcomes, except for knowledge. Although there was a significant (p<0.001) improvement in all 'after' course scores, the only meaningful change (=1 unit) was in knowledge of scrum techniques/rules. Conclusion: Although the only meaningful improvement in 2012 BokSmart course attendees was in one outcome, it should be noted that before-course scores were already high, reducing the questionnaire's ability to assess change because of a ceiling effect. Nonetheless, the knowledge acquisition of these courses was low and not related to previous course attendance or more years of rugby experience. These results justify the biennial nature of this safety course but also indicate that knowledge acquisition is generally low.